Eculizumab as an emergency treatment for adult patients with severe COVID-19 in the intensive care unit: A proof-of-concept study. (November 2020) - Annane, Djillali; Heming, Nicholas; Grimaldi-Bensouda, Lamiae; Frémeaux-Bacchi, Véronique; Vigan, Marie; Roux, Anne-Laure; Marchal, Armance; Michelon, Hugues; Rottman, Martin; Moine, Pierre; ,
Abstract: Background: Complement pathway inhibition may provide benefit for severe acute respiratory illnesses caused by viral infections such as COVID-19. We present results from a nonrandomized proof-of-concept study of complement C5 inhibitor eculizumab for treatment of severe COVID-19. Methods: All patients ( N = 80) with confirmed SARS-CoV-2 infection and severe COVID-19 admitted to our intensive care unit between March 10 and May 5, 2020 were included. Forty-five patients were treated with standard care and 35 with standard care plus eculizumab through expanded-access emergency treatment. The prespecified primary outcome was day-15 survival. Clinical laboratory values and biomarkers, complement levels, and treatment-emergent serious adverse events (TESAEs) were also assessed. Findings: At day 15, estimated survival was 82.9% (95% CI: 70.4%‒95.3%) with eculizumab and 62.2% (48.1%‒76.4%) without eculizumab (log-rank test, P = 0.04). Patients treated with eculizumab experienced a significantly more rapid decrease in lactate, blood urea nitrogen, total and conjugated bilirubin levels and a significantly more rapid increase in platelet count, prothrombin time, and in the ratio of arterial oxygen tension over fraction of inspired oxygen versus patients treated without eculizumab. Eculizumab-associated changes in complement levels, laboratory values, and biomarkers were consistent with terminal complement inhibition, reduced hypoxia, and decreased inflammation. TESAEs of special interest occurring in >5% of patients treated with/without eculizumab were ventilator-associated pneumonia (51%/24%), bacteremia (11%/2%), gastroduodenal hemorrhage (14%/16%), and hemolysis (3%/18%). Interpretation: Findings from this proof-of-concept study suggest eculizumab may improve survival and reduce hypoxia in patients with severe COVID-19. Randomized studies evaluating the efficacy and safety of this treatment approach are needed. Funding: Programme d'Investissements d'Avenir: ANR-18-RHUS60004.